Can immigrant employment alleviate the demographic burden? : The role of union centralization - Alexander Kemnitz (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper investigates the effect of labor immigration on public pensions when wage setting by a centralized trade union leads to unemployment. It is shown that immigration improves the financial soundness of pay-as-you-go pensions if and only if it diminishes total employment. This occurs if the absolute value of the elasticity of labor demand exceeds the unemployment rate.
Keywords: J51; H55; F22; 330; immigration; public pensions; trade union; Einwanderung; Internationale Arbeitsmobilität; Rentenfinanzierung; Gesetzliche Rentenversicherung; Lohnbildung; Gewerkschaftlicher Organisationsgrad; Theorie